Performance and carcass characteristics of lambs fed diets containing different types of carbohydrates associated with polyunsaturated fatty acids - Rafael Lopes Soares; Rita de Cássia Ramos do Egypto Queiroga; Rui José Branquinho Bessa; Francinilda Alves de Sousa; Beatriz Dantas Oliveira Fernandes; Anaiane Pereira Souza; Ariosvaldo Nunes de Medeiros (Acta Scientiarum. Animal Sciences, 2022)
This study aimed to evaluate the productive performance and carcass characteristics of lambs fed diets with different types of carbohydrates associated with polyunsaturated fatty acids. Thirty castrated male lambs (20.5 ± 7.6 kg) were used, distributed in a randomized block design under three experimental diets: High proportion of non-fibrous carbohydrates (NFC) diet; High NFC diet + spineless cactus (high proportion of NFC and spineless cactus) and Low NFC diet (low proportion of NFC), in a 60 day experimental period. The variables of nutrient intake, performance, and carcass characteristics were evaluated. The animals fed the High NFC + spineless cactus diet presented a higher dry matter intake, organic matter, mineral matter, crude protein, and total carbohydrates intake (p <0.05). Carcass characteristics and weight of commercial cuts were improved in High NFC and High NFC + spineless cactus diets (p <0.05), on the other hand we observed a total fat weight reduction in animals fed with High NFC + spineless cactus. The results indicate that high levels of NFC positively influence animal performance, where the type of carbohydrate influences nutrient intake, also affecting carcass characteristics.